2021
DOI: 10.1111/ele.13865
|View full text |Cite
|
Sign up to set email alerts
|

The multidimensional nutritional niche of fungus‐cultivar provisioning in free‐ranging colonies of a neotropical leafcutter ant

Abstract: Foraging trails of leafcutter colonies are iconic scenes in the Neotropics, with ants collecting freshly cut plant fragments to provision a fungal food crop. We hypothesised that the fungus‐cultivar's requirements for macronutrients and minerals govern the foraging niche breadth of Atta colombica leafcutter ants. Analyses of plant fragments carried by foragers showed how nutrients from fruits, flowers and leaves combine to maximise cultivar performance. While the most commonly foraged leaves delivered excess p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(31 citation statements)
references
References 70 publications
0
31
0
Order By: Relevance
“…Specifically, we reason that ant pruning severs connections with the main hyphal network and blocks the flow of nutrients to newly isolated fungal cells. Additionally, previous in vitro studies have observed highest staphylae densities at the lowest nutrient concentrations and after a period of days or weeks suggesting that staphyla formation was preceded by a period of nutrient depletion (17,38,71,73,74). Thus, while the focus on cultivar production typically hinges on optimized nutritional provisioning (17,75,76) We next explore the mechanisms by which nuclei may shape the trajectory of gongylidia development through their spatial distributions in hyphal cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Specifically, we reason that ant pruning severs connections with the main hyphal network and blocks the flow of nutrients to newly isolated fungal cells. Additionally, previous in vitro studies have observed highest staphylae densities at the lowest nutrient concentrations and after a period of days or weeks suggesting that staphyla formation was preceded by a period of nutrient depletion (17,38,71,73,74). Thus, while the focus on cultivar production typically hinges on optimized nutritional provisioning (17,75,76) We next explore the mechanisms by which nuclei may shape the trajectory of gongylidia development through their spatial distributions in hyphal cells.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, previous in vitro studies have observed highest staphylae densities at the lowest nutrient concentrations and after a period of days or weeks suggesting that staphyla formation was preceded by a period of nutrient depletion (17,38,71,73,74). Thus, while the focus on cultivar production typically hinges on optimized nutritional provisioning (17,75,76) We next explore the mechanisms by which nuclei may shape the trajectory of gongylidia development through their spatial distributions in hyphal cells. As the apical portion a gongylidium bulb develops, it is filled with a single large vacuole, which then obstructs nuclear migration and causes the clustering of nuclei at the bulb-filament interface.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fresh fungal cultures of L. gongylophorus were isolated from a Panamanian A. colombica colony (Ac-2012-1) onto potato-dextrose agar (PDA) [20]. Isotopically enriched media were prepared by adding 0.1 g l −1 of 13 C-enriched glucose (D-glucose-1-13 C, Sigma-Aldrich, USA) or 0.1 g l −1 of 13 C-enriched cellulose (U- 13 C Cellulose, U-10508, IsoLife, The Netherlands) to PDA.…”
Section: Methods (A) In Vitro Assaysmentioning
confidence: 99%
“…PDA without enriched compounds was the negative control. Inoculation of the fungus followed established protocols with incubation at 23.5°C [ 20 ]. Polycarbonate track-etched (PCTE) membrane discs (diameter 47 mm, PCTE 0.1 µm; GVS, USA) were placed in Petri dishes to facilitate collection of fungal tissues for subsequent analyses after 79 days.…”
Section: Methodsmentioning
confidence: 99%